Impact of intra-vineyard soil heterogeneity on Malbec. Vine growth, yield and wine elemental composition and sensory profile - Roig-Puscama, Federico; Piccoli, Patricia; Gil, Raúl; Patón, Daniel; Berli, Federico (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
In Mendoza, viticulture is increasingly expanding into mountainous regions, taking advantage of cooler temperatures. High-altitude vineyards, characterized by greater soil heterogeneity, can significantly impact grapevine growth, development, elemental uptake, and wine sensory attributes. Despite its relevance, the effects of intra-vineyard variability on wine organoleptic quality and elemental composition remain underexplored in the existing literature. This study investigated a high-altitude vineyard planted with Vitis vinifera L. cv. "Malbec", focusing on two contrasting soil depth profiles: shallow soil (SS) and deep soil (DS). The DS exhibited a finer texture, higher water retention and greater cation exchange capacity than the SS. Additionally, DS contained higher concentrations of Mn, while SS was richer in Ca. Vegetative growth and yield varied according to soil type and vintage. Wines from DS showed higher [Mn], consistent with the soil, and increased [Fe] and [Cu] compared to SS wines, possibly due to indirect effects. Significant differences were observed in wine organoleptic properties, with SS wines exhibiting greater color intensity, astringency, and structure. Certain aromas, such as cherry and plum were negatively correlated with [Mn]. These findings highlight the influence of vineyard soils on the elemental composition and sensory profiles of wines, providing valuable insights into terroir characteristics for management strategies. Highlights: Intra-vineyard soil heterogeneity significantly affects vegetative growth, elemental composition, and the sensory profile of Malbec wine. Vines in deep soils exhibited greater vigor and produced more clusters per plant than those in shallow soils. Deep soils retain more water, have higher clay and silt content, and produce wines with higher Mn. In contrast, shallow soils are sandier and rockier, with lower water retention, leading to wines with greater color intensity, astringency, and structure.